A natureza como base da ética em Ludwig Feuerbach e Baruch de Espinosa - Sousa, José Alexandre Alves de (2025)
This dissertation aims to analyze nature as the basis of ethics in the works of Baruch de Spinoza and Ludwig Andreas Feuerbach. The purpose of this theoretical approach is to present a critical analysis of the ethics proposed by Feuerbach, aligning it with Baruch de Spinoza's philosophical approach. In addition, it seeks, secondarily, to briefly discuss the relationship between Edgar Morin's educational conceptions and Ludwig Feuerbach's reflections with the aim of promoting a dialogue between Morin's ecological awareness and Feuerbach's naturalistic awareness. Thus, this dialogue sought to reveal a brief contribution to education. To this end, a philosophical investigation was established between the two thinkers, highlighting in a clear and organized way some aspects that permeate their thoughts. For Spinoza, for example, nature is all there is (the totality) and all particular things are modes of substance, so that nothing exists outside of it. This leads to the understanding that we are parts of this totality. Furthermore, it is important to understand that the definition of nature in Spinoza's philosophy is not equivalent to worship of God, but corresponds to the identification between God and nature, hence Deus sive Natura (God or nature). On the other hand, through the prism of Feuerbach's philosophy, a horizon is established through which it is possible to conceive of an ethics of nature based on the relationship between nature and man. The German philosopher, however, does not systematize his reflections on nature, even though he recognizes that it is autonomous and independent. In his interpretation, therefore, there are differences between God and nature, in such a way that nature has autonomy without God, while He is not immanent to nature. In short, although nature is considered, by both Spinoza and Feuerbach, as the foundation and cause of everything, including man, Spinoza's philosophy conceives God and nature as identical, while Feuerbach, in opposition to pantheism, confronts the idea of a God that is contained in nature.